PEMIKIRAN M. QURAISH SHIHAB DAN RELEVANSINYA DENGAN MATERI PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH ATAS PADA KURIKULUM 2013 - Asrul Rohan; Azhar Haq; Ahmad Subekti (VICRATINA, 2019)
This writing is an effort that the direction of Islamic education in Indonesia has not been fully implemented properly. The problem in this research is how intellectual thought Muhammad Quraish Shihab about the material of Islamic Education and how the material of Islamic Education in High School and the relevance of the material of Islamic Education in High School with the Thought of Muhammad Quraish Shihab about Islamic Education in 2013 Curriculum. The hope to be achieved in this study is to be able to provide academic insights for practitioners in the field of Islamic Education, especially those related to Islamic Education material, to be able to add scientific repertoire to the thoughts of Muhammad Quraish Shihab with Islamic Education material and its relevance to Islamic Education material in Senior High School.